DAYA TERIMA ORGANOLEPTIK DAN ANALISIS PROKSIMAT NUGGET IKAN KEMBUNG (Rastrelliger sp.) DENGAN PENAMBAHAN TEPUNG AMPAS TAHU SEBAGAI MAKANAN SELINGAN TINGGI PROTEIN - Ira Putri Winata; Iman Jaladri; Dahliansyah (Jurusan Gizi Poltekkes Pontianak, 2025)
Nuggets are a practical and preferred processed meat product, which can be a solution to increase children's protein intake. High-grade nuggets that use mackerel as the main ingredient, rich in protein and essential fatty acids, can be combined with tofu pulp flour as a utilization of tofu waste that has not been fully utilized by the community and to increase the nutritional value of nuggets. Making mackerel nuggets with the addition of tofu pulp flour can help develop sustainable food products that are beneficial to children's health and the local economy. This study aims to determine the organoleptic acceptability and determine the content of protein, fat, carbohydrates, moisture content and ash content in mackerel nuggets with the addition of tofu pulp flour. This type of research is an experimental design with 4 treatments, namely F1 (95gr:5gr), F2 (90gr:10gr), F3 (85gr:15gr) and F4 (80gr:20gr) mackerel and tofu pulp flour in the manufacture of nuggets. Data analysis for organoleptic tests used the Friedman test conducted by 25 moderately trained panelists at the Pontianak Health Polytechnic Taste Laboratory and proximate analysis at the Pontianak BSPJI Laboratory. The results showed that the tested nuggets had the acceptability of color, aroma, taste and texture in the F2 treatment (90gr:10gr). Nuggets in the best treatment had a moisture content: 57.1%, ash content 1.57%, protein content 9.81%, fat content 1.17%, carbohydrate content 24.5%. There is an effect of aroma and texture on the acceptability of mackerel (Rastrelliger sp.) nuggets with the addition of tofu pulp flour, while on the color and taste acceptability there was no effect of the addition of tofu pulp flour on the mackerel nuggets.